A study of the collapse speed of bubble clusters. (August 2020) - Du, Tezhuan; Wang, Jingzhu; Wang, Yiwei; Huang, Chenguang
Highlights: The key parameters for bubble collapse, including bubble quantity, volume fraction, and dimensionless pressure, are acquired with the assistance of dimensional analysis. The effects of key parameters on collapse of bubble cluster are investigated by direct numerical simulation. The influence of bubble distribution on bubble cluster collapse is discussed. Abstract: The collapse process of bubble cluster is closely related to bubble–bubble interaction. Theoretical analysis and numerical simulation are adopted to study the collapse of bubble cluster with various distributions. The key parameters for bubble collapse, including bubble quantity, volume fraction, and dimensionless pressure, are acquired by dimensional analysis. The effects of key parameters on collapse of bubble cluster are investigated by direct numerical simulation. The numerical result shows that the collapsing speed of bubble cluster increases with the increase of bubble quantity and dimensionless pressure, decreases with the increase of volume fraction. A condensation rate is considered on the basis of bubble cluster with primitive cubic distributions. Square pyramid arrangement and random arrangement of bubbles are also simulated. A parameter study of the dimensionless bubble distance bubble cluster with random arrangement shows that a larger distance generally results in a larger collapse speed of bubble cluster.